Diaspora tourism and well-being: A eudaimonic view - Li, Tingting Elle; Chan, Eric Tak Hin (Annals of tourism research, 2017)
In recent years, subjective well-being (SWB) has attracted growing interest from researchers of travel and tourism, who have investigated the effects of leisure and tourism activities on the individually perceived and experienced well-being of both tourists and host communities. Various terms have been used, sometimes interchangeably, to capture the meaning of SWB, including happiness, life satisfaction, quality of life, etc. Hedonic views of SWB are rife in this literature, with pleasure and satisfaction being seen as the ultimate goal and consequence of various experiences and activities. In this view, the utilities of people are emphasised and their rewards are maximised in terms of happiness and the satisfaction of preferences. However, well-being is more than simple preference satisfaction, and the pleasure-producing outcomes of many behaviours do not necessarily promote well-being. Among recent tourism studies, few have included the aspects of eudaimonia when examining SWB. For example, McCabe and Johnson included the themes of social relationships and self-esteem; and Richards considered personal development and the pursuit of personal and social interests.